Ritus Teing Tinu dan Etika Tanggung Jawab Emmanuel Levinas: (Dialog Kearifan Lokal Manggarai dalam Relasi Keluarga) - Felix Riondi Sugar; Porfirios Samuel Febrian Lembak; Epi Pianus Gregorius Gadja Wora; Anselmus K.A. Blikololong; Alfeus Alfian Nenat; Antonius Sunarno Sam; Apriliano Peterpen Ajen; Benyamin Chintyano Meo; Bernardino Suryatno Agas; Ikordinus P. Wasini (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study examines the relationship between the teing tinu ritual in Manggarai culture and Emmanuel Levinas’ ethics of responsibility as a framework for understanding family relations grounded in care, respect, and moral obligation toward parents. The research employs a qualitative approach using library research methods to analyze cultural texts and philosophical works. The findings show that teing tinu embodies reciprocal responsibility and gratitude within family life, which resonates with Levinas’ concept of asymmetrical ethical responsibility arising from the encounter with the face of the Other. This integration reveals that Manggarai family ethics can be interpreted as an existential relational structure beyond mere ritual practice. The study contributes to intercultural philosophy and local wisdom discourse in Indonesia by offering a dialogue between Western philosophy and indigenous ethics and highlighting relevance for contemporary moral challenges in modern family life especially among younger generations in Manggarai society today in present time.